2020
DOI: 10.3390/ijerph17238722
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal Breast Cancer in Women, Clinical and Epidemiological Factors Related to the Molecular Subtype: A Retrospective Cohort Study in a Single Institution for 13 Years. Follow-Up Data

Abstract: This study focused on the characteristics of postmenopausal breast cancer in the population of southeastern Europe. This retrospective study explored the clinical, epidemiological, and molecular characteristics of women with postmenopausal breast cancer. Material and methods: A retrospective cohort study was performed on 721 postmenopausal breast cancer patients selected from the database of our institution. The data collected consisted of age, living environment, location of the breast tumor, stage of the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…These results are similar to other studies [56][57][58]. In addition, a cohort study also stated that in the middle age group (41-50 and 51-60 years) of postmenopausal women, the Luminal B subtype (ER+, PR+/-, HER2-, Ki-67 14-30%) is the most diagnosed breast cancer in this group, while for the age group (61-70 and 71-80 years) most of the patients had the Luminal A subtype (ER+, PR+, HER2-, Ki-67 < 14%) [59]. It can be caused by the increase in fat tissue in the body, especially in postmenopausal women, causing an increase in the secretion of the hormone estrogen which results in an increased risk of invasive breast cancer with positive ER subtype [60][61][62].…”
Section: Discussionmentioning
confidence: 85%
“…These results are similar to other studies [56][57][58]. In addition, a cohort study also stated that in the middle age group (41-50 and 51-60 years) of postmenopausal women, the Luminal B subtype (ER+, PR+/-, HER2-, Ki-67 14-30%) is the most diagnosed breast cancer in this group, while for the age group (61-70 and 71-80 years) most of the patients had the Luminal A subtype (ER+, PR+, HER2-, Ki-67 < 14%) [59]. It can be caused by the increase in fat tissue in the body, especially in postmenopausal women, causing an increase in the secretion of the hormone estrogen which results in an increased risk of invasive breast cancer with positive ER subtype [60][61][62].…”
Section: Discussionmentioning
confidence: 85%
“…However, our study suggests that basal cells can acquire hybrid features with aging by turning on pathways active in luminal cells during early pubertal development. In support of this model, studies have shown that basal cells can acquire hybrid phenotypes upon transformation 57 and form luminal-like tumors 52,54 , which are the predominant subtypes found in postmenopausal breast cancers 58 . Future work will determine the precise contribution of basal cells to tumor initiation with aging.…”
Section: Discussionmentioning
confidence: 86%
“…There are no prospective randomized data supporting the use of radiation treatment with phyllodes tumors. However, in the setting where additional recurrence would create significant morbidity (e.g., chest wall recurrence following mastectomy), radiotherapy may be considered following the same principles, which are applied to the treatment of soft tissue sarcoma [35][36][37].…”
Section: Case Discussionmentioning
confidence: 99%